2018
DOI: 10.1016/j.ijmedinf.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Physician nurse care: A new use of UMLS to measure professional contribution

Abstract: Background Physician and nurses have worked together for generations; however, their language and training are vastly different; comparing and contrasting their work and their joint impact on patient outcomes is difficult in light of this difference. At the same time, the EHR only includes the physician perspective via the physician-authored discharge summary, but not nurse documentation. Prior research in this area has focused on collaboration and the usage of similar terminology. Objective The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 41 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…16 Additionally, nursing notes describe aspects of the patient’s condition that are not addressed in the flowsheet or other structured data, such as change in status, nursing interventions, and patient responses (ie, precipitating factors of pain, patients’ response to symptom management, or discussion about plan of care in a family meeting). 17 In summary, nurses and physicians focus on different aspects of patient care 18 and need integration of these clinical notes to gain a comprehensive understanding of the patient’s health status.…”
Section: Introductionmentioning
confidence: 99%
“…16 Additionally, nursing notes describe aspects of the patient’s condition that are not addressed in the flowsheet or other structured data, such as change in status, nursing interventions, and patient responses (ie, precipitating factors of pain, patients’ response to symptom management, or discussion about plan of care in a family meeting). 17 In summary, nurses and physicians focus on different aspects of patient care 18 and need integration of these clinical notes to gain a comprehensive understanding of the patient’s health status.…”
Section: Introductionmentioning
confidence: 99%
“…18,38 The most common standard terminologies used were the SNOMED-CT (Systematized Nomenclature of Medicine, approximately 40%, n = 17) [12][13][14]16,22,25,27,29,31,32,36,41,42,45,[51][52][53] and the UMLS (Unified Medical Language System, approximately 35%, n = 15). 9,[12][13][14]19,22,25,[28][29][30]36,41,42,49,51 Nursing standard terminologies, such as the International Classification for Nursing Practice and the Omaha System, were used in only eight studies. 18,25,28,31,33,[35][36][37] Other standard terminologies were also used in some studies including the International Classification of Diseases, 18,25,28,31,33,35,<...…”
Section: Nlp Methodological Approaches Evaluation and Performancementioning
confidence: 99%
“…Nursing documentation differs from documentation by other health providers, including physicians. For example, a recent study found that only 26% of patients' notes in EHRs included synonyms between the physician's and the nurse's clinical notes 9 . Today, there is a major gap in our knowledge regarding the extent to which NLP is applicable to nursing notes.…”
mentioning
confidence: 99%
“…Electronic IT systems should collect all appropriate normalised data generated by health care employees, such as nurses and doctors, in order to improve the quality and effectiveness of services provided to the patients [ 1 ]. Unfortunately, electronic medical records (EMR) may currently not be used to study the independent contribution of nursing to health care outcomes [ 2 ], thus the use of nursing terminology in this project, which will enable not only care planning, but also obtaining medical history and describing the health care status of the patient [ 3 ]. This enables the unification of care and its standardisation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%